2014
DOI: 10.1155/2014/658929
|View full text |Cite
|
Sign up to set email alerts
|

Digital Breast Tomosynthesis Changes Management in Patients Seen at a Tertiary Care Breast Center

Abstract: Objectives. To study factors that predict changes in management with digital breast tomosynthesis (DBT). Methods. The Institutional Review Board approved this HIPAA compliant study. 996 patients had DBT with full field digital mammography (FFDM). Univariate analysis evaluated predictors of management change and cancer detection. Results. DBT changed management in 109 of 996 (11%); 77 (71%) required less imaging. Recalled patients after abnormal FFDM screen were most likely to have management change—25% (24 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
16
0
5
Order By: Relevance
“…These benefits have been shown to be achievable across all breast densities but appear to be especially large in women younger than 50 years (6,7). In addition, Margolies et al (8) found that DBT significantly changed management in women with dense breasts (13% of cases) compared with women with less dense breasts (9% of cases) (P = .03). More recently, McDonald et al (14) have shown that improvements in screening outcomes with DBT were sustainable over consecutive years of screening in an entire clinic population.…”
Section: Conspicuity By Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…These benefits have been shown to be achievable across all breast densities but appear to be especially large in women younger than 50 years (6,7). In addition, Margolies et al (8) found that DBT significantly changed management in women with dense breasts (13% of cases) compared with women with less dense breasts (9% of cases) (P = .03). More recently, McDonald et al (14) have shown that improvements in screening outcomes with DBT were sustainable over consecutive years of screening in an entire clinic population.…”
Section: Conspicuity By Viewmentioning
confidence: 99%
“…Digital breast tomosynthesis (DBT) is rapidly being implemented in breast clinics as the "better mammogram" because it addresses some of the limitations of conventional two-dimensional mammography by alleviating the effect of superimposed structures that lead to both false-positive and false-negative results at breast cancer screening (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…6 DBT became available in 2011 with many studies demonstrating its ability to improve the sensitivity of screening mammography compared with FFDM, while decreasing recall rates. 7 In the setting of diagnostic mammography for palpable mass, DBT is superior to FFDM for the characterization of the margins of masses noted on mammography. This knowledge may aid in differentiating benign from malignant lesions, resulting in fewer biopsies of benign lesions.…”
Section: Diagnostic Mammogram/ Digital Breast Tomosynthesis (Dbt)mentioning
confidence: 99%
“…The ability to view the breast in slices can provide improved lesion visibility within the cross section of the breast tissue. Early in the clinical implementation of DBT, the results of studies promised that DBT would help to improve the accuracy of diagnostic and screening mammography, reduce recall rates, and provide accurate 3D lesion localization [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…When using DBT with FFDM for imaging patients with dense breasts, a proportionally greater advantage was seen when comparing AUCs: 0.877 for DBT with FFDM, 0.786 for FFDM alone, and 0.832 for FFDM with craniocaudal DBT. Margolies and colleagues [19] evaluated a cohort of patients at increased risk of breast cancer and investigated the effect of adding DBT on patient management. They found that patients with BI-RADS category 3 or 4 breast density had a significantly higher likelihood of having DBT findings that changed management (13% of patients with heterogeneously dense or extremely dense tissue vs 9% of patients with fatty or scattered tissue; p = 0.03).…”
Section: Introductionmentioning
confidence: 99%